Angiopoietin‐like 4 promotes angiogenesis in the tendon and is increased in cyclically loaded tendon fibroblasts. (18th January 2016) - Mousavizadeh, Rouhollah; Scott, Alex; Lu, Alex; Ardekani, Gholamreza S; Behzad, Hayedeh; Lundgreen, Kirsten; Ghaffari, Mazyar; McCormack, Robert G; Duronio, Vincent
Abstract : Key points: Angiopoietin‐like 4 (ANGPTL4) modulates tendon neovascularization. Cyclic loading stimulates the activity of transforming growth factor‐β and hypoxia‐inducible factor 1α and thereby increases the expression and release of ANGPTL4 from human tendon cells. Targeting ANGPTL4 and its regulatory pathways is a potential avenue for regulating tendon vascularization to improve tendon healing or adaptation. Abstract: The mechanisms that regulate angiogenic activity in injured or mechanically loaded tendons are poorly understood. The present study examined the potential role of angiopoietin‐like 4 (ANGPTL4) in the angiogenic response of tendons subjected to repetitive mechanical loading or injury. Cyclic stretching of human tendon fibroblasts stimulated the expression and release of ANGPTL4 protein via transforming growth factor‐β (TGF‐β) and hypoxia‐inducible factor 1α (HIF‐1α) signalling, and the released ANGPTL4 was pro‐angiogenic. Angiogenic activity was increased following ANGPTL4 injection into mouse patellar tendons, whereas the patellar tendons of ANGPTL4 knockout mice displayed reduced angiogenesis following injury. In human rotator cuff tendons, the expression of ANGPTL4 was correlated with the density of tendon endothelial cells. To our knowledge, this is the first study characterizing a role of ANGPTL4 in the tendon. ANGPTL4 may assist in the regulation of vascularity in the injured or mechanically loaded tendon. TGF‐β and HIF‐1α comprise two signalling pathways that modulate the expression of ANGPTL4 by mechanically stimulated tendon fibroblasts and, in the future, these could be manipulated to influence tendon healing or adaptation. Key points: Angiopoietin‐like 4 (ANGPTL4) modulates tendon neovascularization. Cyclic loading stimulates the activity of transforming growth factor‐β and hypoxia‐inducible factor 1α and thereby increases the expression and release of ANGPTL4 from human tendon cells. Targeting ANGPTL4 and its regulatory pathways is a potential avenue for regulating tendon vascularization to improve tendon healing or adaptation.